Penerapan Pendidikan Karakter Berbasis Nilai Islam di SD Muhammadiyah 1 Gondrong - Putri, Nur Afifah Dwi Laksana; Zahara, Shafira; Gustiningsih, Firanda; Maududi, Abul A'la Al (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe the implementation of Islamic value-based character education at SD Muhammadiyah 1 Gondrong and to identify the supporting and inhibiting factors influencing its practice. Using a descriptive qualitative method, data were collected through observations, interviews, and documentation involving the principal, teachers, and students. The findings show that character development is carried out through routine programs and habituation activities, such as Qur’an recitation, communal dhuha and dzuhur prayers, the salam smile greeting culture, and Islamic extracurricular activities. These activities effectively internalize religious values, discipline, responsibility, and social awareness. Supporting factors include teacher role modelling, a religious school environment, and administrative support. The main obstacles consist of inconsistent student participation, negative external environmental influences, and limited time for integrating character values into learning. Overall, the implementation of Islamic value-based character education at the school is running well, although stronger collaboration with parents is needed to ensure continuous character development.